Assessment of Agroforestry Practices as a Land Use Option in Atisbo Local Government Area of Oyo State, Nigeria (2005)
The paper examines the adoption of agoforestry practices as a land use option in Atisbo Local Government Area of Oyo State. Data were generated from primary and secondary sources. The primary data were obtained from structured questionnaire and direct interview of farmers in the study area, using purposive simple random sampling technique. Fifteen farmers were randomly sampled from each of the ten cells of Atisbo Farmers Association of Nigeria with 440 members. Data generated were analyzed using descriptive and inferential test statistics. Results show that although perception of farmers on agroforesty practices varied among respondents, out of the various forms of agroforestry being practiced in the study area, the tree crop system was dominant with a modal frequency of 67.3%. It was also discovered that farmers adopted agroforestry practices for various reasons. The most popular of which was the food and financial gains that accrued from the planning of fruit trees. However, paucity of information, bush burning, labour required and non-availability of incentives were considered as major constraints to the practice of agroforestry in the area. Test of hypotheses showed that although there existed significant differences in the type of agroforestry practices among the farmers in the study area (X2 = 39.60; df = 33; Pr = 0.19), there was no significant variation in the perception of agroforestry among the farmers. It was also noted that there was significant enhancement in the soil fertility of the study area through the practice of agroforestry (X2 = 3.81; df = 4; Pt = 0.43): and that there existed significant relationship between agroforestry practices and productivity in the study area (X2= 209.74; df 48; Pr < 0.01). An implication of the findings is that agroforestry presents huge opportunities for food production and developing forestry practices in the study area.